“No Distinction between Contemplating the Created Realities and Contemplating the One God”: The Earliest Chinese Natural Theology (Journal for the Study of Religion and History (JSRH), 2025)
The Church of the East sent its missionaries to China in the seventh century. As the earliest Christian presence in pluralistic and scientific-techno China, they not only remained faithful to their theological tradition but also creatively engaged in natural theology to demonstrate to the polytheistic Chinese people the existence of one God. This paper argues that Jingjiao’s earliest natural theology in Chinese bridged between the Greek concept of kosmos and Chinese cosmology and cosmogony. This paper will begin by surveying natural theology and the development of the concept of ziran 自然 in the Chinese context. Next, the paper will analyze the texts of the Jingjiao documents, and present its natural theology. Then, the paper studies the continuity between Jingjiao and the Church of the East in terms of its Greek learning. Finally, the significance of Jingjiao’s theology toward the interdisciplinary study of theology and science.
Keywords: Natural Theology, Jingjiao, kosmos, ziran